The Total Origins of the Scientific and practical combined perspectives In Surat Al-Anam Through Al-Manar interpretation(From the first to the tenth origin) An objective study - Issa , Fakhir (Islamic Sciences Journal, 2023)
This research is an explanation, and clarification of the complete scientific and practical principles of beliefs, virtues, and etiquette, as well as ritual and legal acts of worship, and the prohibitions that were mentioned in Surat Al-Ana’m. Sheikh Muhammad Rashid Rida worked on his interpretation to devise these complete principles, to show the axes of the surah and what it contains of rulings, and this in turn It is easy for the reader to reflect on the book of God, as the surat Al-Anaam is the surah of the doctrines, and if it is named the surahs of the Qur’an in a way that indicates what is included in each surah or the most important of it, this surah was called Surah Aqeed Al-Islam, or Surah al-Tawheed. It is detailed for the doctrine of monotheism with its evidence and to respond to the suspicions of unbelievers on monotheism and the consequent destruction of the structures of polytheism and undermine its pillars, and to prove the message and revelation and refute their suspicions, and to compel them to argue the Great Sign of God. It is the Qur'an that includes many verses of mental and scientific matters, and set out the functions of the Messenger and his call and gift in people of different classes and conditions, and for resurrection .And the reward, the promise and the promises, and the conditions and works of believers and unbelievers, and the origins of religion and its universal commandments in virtues and etiquette.